Determinasi Faktor yang Mempengaruhi Tingkat Kemiskinan Kota/Kabupaten Wilayah Mataraman Jawa Timur ditinjau dari Maqasid Syariah - Fitriyanto, Doni (Universitas Islam Kadiri, 2024)
This research investigates the factors influencing poverty levels in the cities and districts of the Mataraman region, East Java Province, within the framework of Maqasid Sharia. Employing a quantitative approach and secondary data analysis from 2018-2023. The data analysis technique used is multiple linear regression with the assistance of EViews 13 software to test the research data. The study focuses on education, Gini ratio, minimum wage, and Regional Gross Domestic Product (GDP) as variables affecting poverty. The findings indicate that education negatively impacts poverty, the Gini ratio correlates positively, minimum wage negatively affects poverty, while GDP shows a negative impact, albeit not significant. These results underscore the importance of education, income equality, adequate wages, and inclusive economic growth in poverty reduction efforts, aligned with the goals of Maqasid Sharia. The study recommends further exploration into health, financial access, and qualitative methods to enhance understanding and policy recommendations. Integrating Sharia economic principles could offer unique solutions in poverty eradication efforts.